Determining Soil Properties using Vertical Electrical Sounding: The Case Study of the Power Electrical Station Project in Al-Debony, Iraq - Al-Khalidy, Amer A. (Engineering, Technology & Applied Science Research, 2025)
A one dimensional electrical survey was carried out in Al-Debony District, about 30 km from the west of Wassit Governorate center. The survey includes three profiles of 30 m long. Each of these profiles consists of three Vertical Electrical Sounding (VES) stations with a separation distance equal to 10 m. The Schlumberger array is used in this paper according to the aim of the study. All obtained data were processed using IPI2WIN software to get the best match between the field curve (after their smoothing) and the theoretical one. The given types of VES curves, for all stations, are shown as HK, KQQ, KHK, HKQ, and HKH. The soil and the presence of different types of water caused a change in electrical resistivity, which is why these curves differed in type. The findings revealed that each sounding station has four to five zones, which illustrate how the resistivity values change with depth. In addition to the salty water and the depth relationship, the low readings indicate the existence of clay layers. Some VES have high resistivity values, suggesting the presence of sand and silt sediments with reduced water salinity as depth increases. Some VES have high resistivity values, which indicate the presence of sand and silt sediments with reduced water salinity as depth increases. There was a good agreement between the data obtained and the information provided from the soil test and borehole sampling. On the other hand, because of the layer's deposition, the salt of the water, and the impact of the lower water table, the topsoil and center portion of the site have high resistivity values.